2020
DOI: 10.15345/iojes.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The Views of Preschool Pre-service Teachers, In-service Teachers and Parents on Pre-School Education of Values

Abstract: The purpose of this study was to investigate the opinions of preschool pre-service teachers, in-service teachers and parents on pre-school education of values. A survey method was used, in which the sample was determined by convenience sampling and consisted of 160 teachers employed in preschool institutions, 276 parents with at least one child attending pre-school education, and 304 preschool teacher candidates. Three written opinion forms including open-ended questions developed by the researchers were used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…The 5E learning model is one of the learning models that provides the possibility to use different methods and techniques in a class environment, is identified with the constructivist learning approach and can be used efficiently in science education (Hun, 2017). There are studies in the literature that have shown that the 5E learning model improves students' attitudes, success, motivation, meaningful learning, and conceptual understanding (Aktas, 2013;Bilgin et al, 2013;Campbell, 2006;Ceylan & Geban, 2009;Putra et al, 2018;Qarareh, 2012;Yalcin & Bayrakceken, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 5E learning model is one of the learning models that provides the possibility to use different methods and techniques in a class environment, is identified with the constructivist learning approach and can be used efficiently in science education (Hun, 2017). There are studies in the literature that have shown that the 5E learning model improves students' attitudes, success, motivation, meaningful learning, and conceptual understanding (Aktas, 2013;Bilgin et al, 2013;Campbell, 2006;Ceylan & Geban, 2009;Putra et al, 2018;Qarareh, 2012;Yalcin & Bayrakceken, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ülkemizdeki çalışmalar genellikle fen bilimleri alanında yapılmakta, matematik alanına yönelik araştırmaların kısıtlı ölçüde olduğu görülmektedir (Saraç, 2017). 5E döngüsü modeli ile ilgili alan yazındaki çalışmalar incelendiğinde; 5E modeline yönelik uygulayıcı ve öğrencilerin düşünceleri (Ayvacı & Bakırcı, 2012;Bilgin vd., 2013;Demir & Maskan, 2014;Feyzioğlu & Demirci, 2013;Yalçın & Bayrakçeken, 2010), uygulayıcıların modeli içselleştirme durumları (Başkan vd., 2007;Bozdoğan & Altunçekiç, 2007), 5E modelinin ilgi, tutum vb. faktörlere etkileri (Demir & Maskan, 2012;Özaydın, 2010;Şaşmaz-Ören & Tezcan, 2009;Temel vd., 2012) ve alanyazın incelemesi (Keleş, 2010;Özmen, 2004;Türkmen, 2006) gibi araştırmalar yapıldığı belirlenmiştir.…”
Section: E Döngüsü Modeliunclassified